Pengaruh Sistem Pengendalian Internal, Digitalisasi Keuangan, dan Efisiensi Pengelolaan Keuangan terhadap Good University Governance - Asrianti; Reynilda; Giri Dwinanda (Lembaga Teewan Journal Solutions, 2026)
This study aims to analyze the influence of the Internal Control System, Financial Digitalization, and Financial Management Efficiency on Good University Governance at Buton Muslim University. This study uses a quantitative approach with a survey method. The population in this study is the academic community and administrative staff involved in university financial management. The research sample of 80 respondents was determined using a purposive sampling technique. Data collection techniques were carried out by distributing questionnaires with a Likert scale. Data analysis methods used validity tests, reliability tests, descriptive analysis, multiple linear regression, t-tests, F-tests, and coefficients of determination (R²) with the help of the SPSS version 26 application. The results show that the Internal Control System has a positive and significant effect on Good University Governance. Financial Digitalization also has a positive and significant effect on Good University Governance. In addition, Financial Management Efficiency has a positive and significant effect on Good University Governance. Simultaneously, the Internal Control System, Financial Digitalization, and Financial Management Efficiency have a positive and significant effect on Good University Governance. This study shows that strengthening internal control, optimizing digital financial systems, and efficient budget management are important factors in improving transparent, accountable, and effective higher education governance.